Turning Requires Plucking: The Role of Understanding in Igbo Conceptualization of Translation (Impact: Journal of Transformation, 2022)
This paper centers on one of the conceptual metaphors that is evoked schematically in conceptualizing translation by the Igbo speaker. Understanding is Grasping is conceptualized in Igbo as Understanding is Plucking. This discussion is based on the assumption that whenever a concept is invoked in a discourse setting, several other sub-schemas are evoked. The apprehension of a concept requires contextual information which is supplied by the conceptual substrates. In particular, if the discussants are people from different cultural orientations and social contexts. Several people have written on the subject of conceptual metaphors so this work focuses on the concept of ghọta ‘pluck’ as one of the metaphors activated in the cognitive environment of the Igbo speaker whenever the concept of translation is evoked. The research was conducted in the South-eastern part of Nigeria where the Igbos are located predominantly and the language data was collected using questionnaires. The sample population for the questionnaire survey consisted of one hundred and fifty (150) respondents both male and female selected through purposive sampling. Also, the questionnaire was designed following an open-ended format as it requires translation of English expressions culled from translation training materials. The respondents were required to translate these English expressions into the Igbo language. Further, the cognitive grammar theory (CG) was adopted as a theoretical framework for data analysis. This linguistic theory leans extensively on cognitive linguistic approach. The findings show that nghọta ‘plucking’ is crucial in the Igbo conceptualization of translation. The detailed discussion of the issues introduced here is found in the doctoral dissertation on, the Igbo conceptualization of ntụgharị ‘translation’.